Integrasi Tafsir Teologi dan Tafsir Sufistik dalam Menjawab Problem Keagamaan Kontemporer: Analisis Karakteristik, Metodologi, dan Relevansinya - Muhammad Baharuddin; Halimah Basri; Muhammad Irham (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This paper examines theological interpretation (tafsir theologis) and Sufi interpretation (tafsir sufistik) as two approaches to Qur'anic exegesis that possess distinct characteristics, methodologies, and orientations while complementing one another in understanding the messages of the Qur'an. Theological interpretation primarily aims to strengthen Islamic creed (aqidah) through rational and textual approaches in explaining concepts of divine attributes, prophethood, predestination, and other theological issues. In contrast, Sufi interpretation focuses on uncovering the inner (esoteric) meanings of the Qur'an through spiritual contemplation and self-purification without neglecting the outward (exoteric) meanings of the verses. This study aims to explain the concepts and characteristics of these two exegetical approaches, examine their respective methodologies, and analyze their relevance in addressing contemporary religious issues. The research employs a qualitative approach using library research as its primary method. Data were collected from classical and contemporary literature on theological and Sufi Qur'anic exegesis and analyzed using a descriptive-analytical method by examining, comparing, and interpreting the views of Muslim scholars and contemporary academics. The findings indicate that theological interpretation provides a systematic foundation for Islamic doctrine, whereas Sufi interpretation enriches the spiritual and ethical dimensions of religious life. The integration of these two approaches offers a comprehensive, moderate, and contextual understanding of the Qur'an that remains relevant to the challenges of contemporary society.